PRINSIP KEHATI-HATIAN DALAM PENYELENGGARAAN SISTEM ELEKTRONIK DALAM UPAYA PERLINDUNGAN DATA PRIBADI DI INDONESIA - Rai Mantili; Putu Eka Trisna Dewi (Jurnal Aktual Justice, 2020)
One of the aspects that must be of concern in electronic transaction activities is the aspect of personal data protection so that the personal data of service users is maintained. One of the principles that must be observed by Electronic System Operators in protecting personal data is the principle of prudence. This paper will examine the principles of prudence in the operation of electronic systems in efforts to protect personal data in Indonesia by using normative research methods. In general, it can be seen that the precautionary principle is not explicitly regulated in the formulation of laws and regulations related to Electronic Information and Transactions or Personal Data Protection, but the provisions of the articles therein contain provisions regarding the principle of prudence. The application of the precautionary principle is carried out with the active efforts of electronic system administrators as the party that manages the personal data of service users to ensure data confidentiality and the security of their electronic systems with all efforts to prevent the system from being compromised by third parties. The legal consequence is that if there is a leak of personal data, the electronic system operator is obliged to be responsible civilian by paying compensation on the basis of a lawsuit by the owner of the personal data who has experienced data leakage and / or material or immaterial loss